Application of deproteinized bovine bone mineral as proangiogenic scaffold for alveolar bone formation in beagle dogs. (2nd February 2021) - Ogasawara, Keita; To, Masahiro; Liu, Yu-Hao; Okudera, Toshimitsu; Nakamura, Takatsuna; Matsuo, Masato
Abstract: Alveolar bone repair after tooth extraction is essential after oral surgeries. Various grafting materials are used to promote the regeneration of lost alveolar bone. This study analysed the morphological features of the tissue regeneration process using deproteinized bovine bone mineral (DBBM). DBBM was used to densely fill the extraction sockets in beagle dogs. Following resin casting of the vasculature, stereomicroscopy and scanning electron microscopy were used to observe blood vessels and hard tissues in haematoxylin and eosin-stained sections on postoperative days 14, 30 and 90 in conjunction with vascular endothelial growth factor (VEGF) immunostaining to evaluate alveolar bone vascularization. On day 14 post-operation, the DBBM granules tightly filled the extraction sockets, maintained alveolar margin height and formed a scaffold for aiding angiogenesis and new bone formation. On day 30, new bone formation was observed around the DBBM granules. By day 90, bone tissue regeneration progressed in both groups but was more pronounced in the DBBM group. Alveolar margin height was maintained in the DBBM group throughout the study. Furthermore, VEGF expression in the DBBM group was detected around newly formed bone. We conclude that DBBM acts as a suitable scaffold for new bone generation, as well as angiogenesis around healing alveolar bone, and that it has the potential to play a key role in vascularization and bone formation.